2004
DOI: 10.1128/aem.70.7.4211-4215.2004
|View full text |Cite
|
Sign up to set email alerts
|

Host-AdaptedCryptosporidiumspp. in Canada Geese (Branta canadensis)

Abstract: The prevalence and distribution of Cryptosporidium spp. in the fecal droppings of the free-living waterfowl Canada geese were examined at 13 sites in Ohio and Illinois. On the basis of the analysis of the small-subunit rRNA gene by PCR, followed by restriction fragment length polymorphism analysis and DNA sequencing, 49 (23.4%) of 209 fecal specimens collected from 10 sites (76.9%) were positive for Cryptosporidium spp. The following five Cryptosporidium species and genotypes were identified: Cryptosporidium g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
86
2
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 107 publications
(92 citation statements)
references
References 25 publications
3
86
2
1
Order By: Relevance
“…C. galli was first described by Pavlásek in hens, and later this species was re-described (Ryan et al, 2003). In contrast, the duck genotype has a limited host range, having only been found in a black duck (Anas rubripes) and Canada geese (Branta canadensis) (Jellison et al 2004;Zhou et al, 2004).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…C. galli was first described by Pavlásek in hens, and later this species was re-described (Ryan et al, 2003). In contrast, the duck genotype has a limited host range, having only been found in a black duck (Anas rubripes) and Canada geese (Branta canadensis) (Jellison et al 2004;Zhou et al, 2004).…”
Section: Methodsmentioning
confidence: 99%
“…Thus far, four Cryptosporidium species/genotypes have been identified in chickens and ducks, including C. meleagridis, C. baileyi, C. galli, and the duck genotype (Slavin, 1955;Current et al, 1986;Morgan et al, 2001;Ryan et al, 2003;Jellison et al, 2004;Zhou et al, 2004;Amer et al, 2010). Among the species/genotypes, C. baileyi was originally isolated from commercial broiler chickens and is probably the most common avian Cryptosporidium species.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…and genotypes from Canada geese collected from 13 sites in Ohio and Illinois; goose genotype I, goose genotype II, the duck genotype, C. parvum and C. hominis (Zhou, et al, 2004). Phylogenetic and sequence analysis of the SSU rRNA gene has revealed that goose genotypes I and II and the duck genotype are closely related.…”
Section: Goose Genotypes I-ivmentioning
confidence: 99%
“…Microscopic analysis of hematoxylin and eosin (H & E) stained sections from the black duck indicated an enteric infection with numerous oocysts attached to the apical surface of the enterocytes of the small intestine but clinical information on this bird was not available. The duck genotype has subsequently been identified in Canada geese (Branta canadensis) (Jellison, et al, 2004, Zhou, et al, 2004). …”
Section: Duck Genotypementioning
confidence: 99%